Meningkatkan Aktivitas Belajar Lisan Mahasiswa PGSD Menggunakan Metode Group Investigation - Husnul Khatimah; Mustadi, Ali; Meivawati, Eli; Anas, Munawir (Celebes Journal of Elementary Education, 2024)
This classroom action research aims to improve oral learning activities in elementary school teacher education students at Yogyakarta State University by applying the group investigation model in the mathematical concept course in the early grades. The subjects of the study consisted of 39 students. Data collection was carried out through observation techniques. Data validation used time triangulation and expert judgment techniques. The results of the study showed an increase in oral learning activities after the application of the group investigation model, which was reflected in the increase in three leading indikators, namely the activity of asking questions increased by 12.11%, the activity of answering increased by 6.82%, and the activity of expressing opinions increased by 24.36%. Based on the increase in each aspect of oral learning activities, the application of the group investigation model effectively improves the oral learning activities of elementary school teacher education students at Yogyakarta State University in the mathematical concept course in the early grades.